2019
DOI: 10.1038/s41598-019-39450-5
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the response to global warming in a heat-sensitive species

Abstract: Avoiding hyperthermia entails considerable metabolic costs for endotherms. Such costs increase in warm conditions, when endotherms may trade food intake for cooler areas to avoid heat stress and maximize their energy balance. The need to reduce heat stress may involve the adoption of tactics affecting space use and foraging behaviour, which are important to understand and predict the effects of climate change and inform conservation. We used resource selection models to examine the behavioural response to heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 74 publications
3
40
0
Order By: Relevance
“…Ambient temperature was repeatedly shown to be one of the most important factors affecting the activity rhythms (Maloney et al 2005;Pagon et al 2013;Brivio et al 2016Brivio et al , 2017Grignolio et al 2018) and spatial behaviour of ungulates (Mysterud and Østbye 1999;Marchand et al 2015;Mason et al 2014Mason et al , 2017. By reducing activity when it is warmer and selecting cooler microclimates in their environment (Mysterud and Østbye 1999;Marchand et al 2015;Brivio et al 2019), animals may be able to avoid heat stress, while reducing the costs for autonomic thermoregulation (Terrien et al 2011). Our results are consistent with these findings and suggest that temperature strongly affected the behavioural strategies of the monitored individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient temperature was repeatedly shown to be one of the most important factors affecting the activity rhythms (Maloney et al 2005;Pagon et al 2013;Brivio et al 2016Brivio et al , 2017Grignolio et al 2018) and spatial behaviour of ungulates (Mysterud and Østbye 1999;Marchand et al 2015;Mason et al 2014Mason et al , 2017. By reducing activity when it is warmer and selecting cooler microclimates in their environment (Mysterud and Østbye 1999;Marchand et al 2015;Brivio et al 2019), animals may be able to avoid heat stress, while reducing the costs for autonomic thermoregulation (Terrien et al 2011). Our results are consistent with these findings and suggest that temperature strongly affected the behavioural strategies of the monitored individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that higher elevations may constitute less stressful habitats for L. picturatus and L. externus is consistent with some broader trends in elevational dynamics of species distributions. It is understood that mountain‐top habitats serve as refugia for many cold adapted species (Brivio et al., 2019; Hampe & Jump, 2011; Hering et al., 2009). Species that have evolved to conditions found at high elevations will require cooler temperatures (or other abiotic variables associated with high‐elevation habitats) while hot environments associated with lower elevations will likely be stressful, resulting in lower elevation boundaries that are controlled by abiotic variables.…”
Section: Discussionmentioning
confidence: 99%
“…In Alpine ibex, the thermoregulation-foraging trade-off is a pivotal driver of spatio-temporal variation in animal distribution (Brivio et al, 2019;Mason, Brivio, Stephens, Apollonio, & Grignolio, 2017). It has been shown that this trade-off varies across the seasons: thermoregulation appears to override forage productivity in importance when temperatures are high (i.e., August: Mason et al, 2017;Brivio et al, 2019). Overall, the results of these studies strongly indicate the need of further research to disentangle how ibex deal with the trade-offs among the avoidance of overheating, food acquisition and reduction in predation risk.…”
Section: Discussionmentioning
confidence: 99%